2015
DOI: 10.1007/s12517-015-1970-9
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentological, mineralogical, and geochemical characterization of sand dunes in Saudi Arabia

Abstract: This paper investigates the morphology, texture, composition, mineralogy, and geochemistry, and provenance of sand dunes from 10 locations in Saudi Arabia. Morphologically, these sand dunes include linear, parallel to subparallel ridge, parabolic, barchans, and star sand dunes. Sixty-seven samples were collected from these different sand dune types. Generally, sands from dunes in all locations were characterized by fine to coarse mean grain size, were moderately sorted, and had near symmetrical skewness with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…In contrast to the loess deposits of the Negev Desert and the topsoil sediments of the Judean Mountains, the sediments of Section 9 have an additional third mode in the fine sand fraction which is comparable to aeolian sand deposits in the Arava/Araba Valley to the west of the central Jordanian Plateau or to dune sands in northeastern Saudi Arabia in its east (Saqqa and Atallah, 2004;Benaafi and Abdullatif, 2015; Figure 5). Thus, this coarser grain population probably represents locally derived aeolian sand.…”
Section: The Depositional Setting At Jurf Ed Darawishmentioning
confidence: 99%
“…In contrast to the loess deposits of the Negev Desert and the topsoil sediments of the Judean Mountains, the sediments of Section 9 have an additional third mode in the fine sand fraction which is comparable to aeolian sand deposits in the Arava/Araba Valley to the west of the central Jordanian Plateau or to dune sands in northeastern Saudi Arabia in its east (Saqqa and Atallah, 2004;Benaafi and Abdullatif, 2015; Figure 5). Thus, this coarser grain population probably represents locally derived aeolian sand.…”
Section: The Depositional Setting At Jurf Ed Darawishmentioning
confidence: 99%
“…Provenance of Arabian sandstones and sands has been studied using petrographic, heavy-mineral, U-Pb zircon dating (Garzanti et al, 2013(Garzanti et al, , 2017, and geochemical methods (Benaafi & Abdullatif, 2015). Paleozoic sandstones (and Mesozoic, to lesser extent) have been suggested to be the main source of sand in the Nafud, Dahna, and the western part of AlRub'AlKhali deserts (Garzanti et al, 2013(Garzanti et al, , 2017.…”
Section: Radwan Et Almentioning
confidence: 99%
“…The values of d m were 336.32 μm for SR sample and 322.17; 283.91; 303.21 and 319.62 μm for SE, SN, SW and SS respectively. Studying sedimentological, mineralogical and geochemical characterization of sand dunes in Saudi Arabia, Benaafi and Abdullatif [19] reported that sand dunes from Tayma area (Not so far from Madâin Sâlih archeological area) showed the coarse mean grain size, the mean diameter is 250-350 μm. In Figure 5, we plotted on the y axis the cumulative percent passing and on the x axis the logarithmic sieve size.…”
Section: Grain Size Distribution Analysis and Specific Gravitymentioning
confidence: 99%